Leadership Development's Epic Fail - McNulty, Eric J. (MIT Sloan Management Review, 2017)
As busy as they are, leaders need to find ways to observe fundamental work processes in their organizations. When they do, they usually discover that there are gaps between theory and reality in how works get done. Michael Morales' experience - in which identifying and addressing such gaps led to his company saving $50,000 in just 60 days - is a case in point.